Neuroanatomy of spinal nociception and pain in dogs and cats: a practical review for the veterinary clinician - Pedersen, Tenna Remler; Berendt, Mette; Rusbridge, Clare (Frontiers in Veterinary Science, 2025)
Chronic pain is a prevalent condition in companion animals and poses significant welfare challenges. To address these concerns effectively, veterinary clinicians must have a comprehensive understanding of the neuroanatomy of nociception and the intricate processes underlying pain perception. This knowledge is essential for planning and implementing targeted treatment strategies. However, much of the existing information on pain mechanisms is derived from studies on rodents or humans, highlighting the need for further translational research to bridge this gap for veterinary applications. This review aims to provide veterinary clinicians with an in-depth overview of the spinal nociceptive pathways in the dog and cat, tracing the journey from nociceptor activation to cortical processing in the brain. Additionally, the review explores factors influencing nociceptive signaling and pain perception. By enhancing the understanding of these fundamental physiological processes, this work seeks to lay the groundwork for developing effective therapies to manage the complexities of chronic pain in companion animals.